Evaluation of interseeded grain sorghum and soybeans as a silage crop - Esmail, S.H.M.; Hartadi, H.; Harbers, L.H.; Shirley, John E.; Hoover, J.D.; Azimi, S.; Pfaff, L.W.; Bolsen, K.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Interseeded grain sorghum and soybeans have been evaluated as a silage crop over a 3year period. In the first 2 years, maximum dry matter (DM) yields occurred at the late-dough stage of the grain sorghum, and interseeded silages had higher crude protein (CP) and acid detergent fiber contents than non-interseeded late-dough stage, grain sorghum control silages. In year 2, seeding grain sorghum and soybeans in alternating IS-inch rows increased DM yield, CP content, and the proportion of soybean plants in the mixture compared to drilled (6-inch spacing) interseeding. Digestibilities of most nutrients were similar in all silages; however, cattle fed control silage consumed the most DM in year 1, but not in year 2. In both years, calves fed the control silages had faster gains than those fed drilled sorghum-soybean silages. Adding grain improved gain and intake only for calves fed the interseeded silage in year 1. In year 3, seeding grain sorghum and Williams 82 soybeans in alternating rows did not increase DM yield over the drilled interseeding. However, the drilled mixture had a much higher proportion of soybean plants compared to the first two years. All mixtures had higher CP content than control grain sorghum.
Keywords: Beef; Sorghum; Soybeans; Silage